On the specific features of the spectrum of eigenmodes of elastic bodies - Grinchenko, V.T.; Gorodetska, N.S. (Reports of the National Academy of Sciences of Ukraine, 2018)
An analysis of the characteristics of the resonance on inhomogeneous waves with symmetric vibrations of a semi-infinite plate with free lateral boundary and free end is carried out. At the frequency of the edge resonance, the first propagating normal wave is formed by the superposition of propagating SV-wave and an inhomogeneous P-wave. Qualitatively, the edge resonance is due to the peculiarities of the reflection of elastic waves from the free boundary.